Durability of different glass coatings in humid and saline environments, ageing impact on heat-light transmission and thermal comfort. (15th August 2016) - Stazi, F.; Giampaoli, M.; Tittarelli, F.; Di Perna, C.; Munafò, P.
Abstract: The present study investigates the durability of different types of glass coatings (four solar control, two low-emissivity and one self-cleaning) with various metal compositions. In the experimental phase, physical, chemical, optical and energy properties were evaluated, before and after two ageing treatments: hot-wet and salt-spray. In the numerical phase, the energy performance of a double glazing with the selected coatings were compared by adopting an office room as case study. Heating, cooling, artificial lighting consumptions, solar gains, daylighting factors and summer comfort levels were analysed. Further, the environmental impact in the use phase was assessed. The salt-spray environment resulted to have the highest incidence on the film performance. In the physical and chemical tests, the worst resistance was shown by the coatings with the highest silver percentages, with consequent significant decay of the light transmittance. The films with niobium and titanium showed the best durability. On the other hand, the silver-based coatings demonstrated the best solar selectivity and the highest performance in term of energy consumptions, comfort levels and CO2 emissions, both before and after ageing. Highlights: Comparison between seven types of glass coatings. Adoption of two artificial ageing: hot-wet and salt-spray. The salt-spray environment has the highest incidence. High Ag percentages show the worst durability and the highest energy saving. Silver weight should be lower than 60% of the total film weight.